2016
DOI: 10.1080/00016489.2016.1204663
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance volumetric measurement of endolymphatic space in patients without vertiginous or cochlear symptoms

Abstract: Among all patients, the mean ELS/the total fluid space (TFS) ratio in the cochlea was 8.8% and that in the vestibule was 16.2%. The ELS in the cochlea and vestibule was classified into four categories. Age-related differences were found in the TFS, ELS, and ELS/TFS ratio in the inner ear and the ELS and ELS/TFS ratio in the vestibule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In the present study, we also observed changes in EH using conventional two-dimensional evaluation (Nakashima's criteria) and could not find a relationship between vertigo suppression and EH. Then, we attempted volumetric measurement of the ELS as reported by our group previously (19). In the present study, 80.0% of patients experienced relief from vertigo after ELSD (vertigo–).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we also observed changes in EH using conventional two-dimensional evaluation (Nakashima's criteria) and could not find a relationship between vertigo suppression and EH. Then, we attempted volumetric measurement of the ELS as reported by our group previously (19). In the present study, 80.0% of patients experienced relief from vertigo after ELSD (vertigo–).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the volume of ELS and ELS ratio of controls that had never experienced vertigo/dizziness and never suffered ear disease; the volume of ELS in controls was 10.3 ± 6.9 μl (average ± standard deviation) in the cochlea and 11.5 ± 7.1 μl in the vestibule. The ELS ratio in the cochlea was 8.8 ± 5.3 and that in the vestibule was 16.2 ± 9.0 (19). Compared with the controls, the ELS ratio of vertigo– patients was still higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of v‐EH% widely ranged from 3.2% to 64.1%, and the median was 18.1% in this study group. The v‐EH% of patients without vertiginous or cochlear symptoms was reported to be 16.2% . This number is only a reference for healthy subjects because the study group consisted of patients with chronic rhinosinusitis, but the median value in our study group was larger than this reference value.…”
Section: Discussionmentioning
confidence: 67%